Desain struktur kawat penyangga ambalan - Centaury Harjani; Chrismastuti Nur (PRODUCTUM Jurnal Desain Produk (Pengetahuan dan Perancangan Produk), 2019)
Wall shelf is one of furniture that is widely used nowadays. A wall shelf which is designed to utilize the vertical area of the house becomes a favorable choice because of its minimalist and space saving design. The wall shelves design on the market usually has a metal retaining frame. Certain designs use L-brackets support structures, however, some of them do not use it at all. Most L-brackets are made of metal material from industrial mass production. Actually, design of a wall shelf can be made using a wire retaining structure. Wire material can be used as a support structure that is able to withstand loads. This research used experimental method to explore several supporting structure designs of wire material. Manual techniques such as twisting technique, coiling technique, and bending technique were combined to increase strength of the wire. Various exploration results were tested to determine firmest structure with the most efficient material. This article is expected to revive the tradition of craftsmanship and to inspire young designers to be creative in developing wire product design.Key words: wall shelf, structure design, wire design, wire structure